Mediasi Ekuitas Merek dalam Pengaruh Strtgi Customer Relationship Marketing terhadap Loyalitas Nasabah (Studi pada Bank BNI dan BCA di Jawa Timur) - Iriani, Sri Setyo (Jurnal Aplikasi Manajemen, 2009)
This study aims at integrating the causality model between customer relationship strategy, brand equity and customer loyalty at government owned banks and private banks in East Java. The research location is the BNI 46 and BCA main branches in 5 (five) ex East Java Districts, i.e. Surabaya, Kediri, Madiun, Tuban, dan Jember. The research sample includes the two banks, BNI 46 and BCA banls in the five areas: Surabaya, Kediri, Madiun, Tuban, and Jember. The number of samples is 105 customers are from BNI 46 and the other 105 customers are from BCA. To test the research hypothesis 2 conceptual models were developed. Furthermore the data were analyzed using descriptive statistic and structural equation model (SEM). Based on the descriptive statistical analysis and loading factor, it was shown that there is no CRM strategic differences, as told by the customers of both banks, BNI 46 and BCA, because the customers give high (positive) value to all the CRM strategy indicators of the banks they deposit their money, and in fact the shared value indicator gets the highest score and trust is the significant determinant for the customers in doing total evaluation by the bank customers showed that the brand equity of both BNI 46 and BCA get positive score. For BNI 46 customers the brand equity which was strongly felt was quality impression while for BCA customers it was brand association. In the total evaluation of the bank brand equity, both BNI 46 and BCA customers did not give different scores: the customers of the two banks showed that brand awareness level has the highest loading factor. Moreover, the customers of both BNI 46 and BCA showed high loyalty to the banks they save their money. For BNI 46 customers their loyalty was shown by their the length of time of being BNI 46 customers, while for BCA customers their loyalty as shown by their willingness to recommend other people to use BCA service. In the total loyalty evaluation the customers of both banks give different scores. For BNI 46 customers, BNI 46 is the first banks they use for financial transaction while for BCA customers the loyalty was shown by their willingness to recommend other to use BCA services. Based on the hypothesis testing using SEM, it was proved that the close relationship which was formed through the application of CRM strategy could strengthen bank brand equity for the application of CRM strategy could strengthen bank brand equity for their customers. The application of CRM which forms close relationship with the customers proved to strengthen the customers loyalty to the banks. Although banks are able to put the brand strength in the customers' mind, its effect will gradually reduced unless at the same time the banks also apply effective CRM strategy. Customers prefer direct, interaction or touch through CRM strategy to the banks' effort to put the bank brand strength in their mind.